Design of a Height and Weight Measurement Tool for Toddlers at Spreadsheet-Based Posyandu - Laksono Hadi, Moch. Faizal; Sulistiyowati, Indah; Jamaaluddin, Jamaaluddin; Anshory, Izza (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2023)
When it comes to disease prevention and quality human development, the main focus is on promoting optimal under-five health and growth. Integrated service posts, also known as posyandu, often take center stage when it comes to tracking the development of under-fives in the community. However, there is still no effective system to measure the height and weight of toddlers in posyandu. Therefore, a spreadsheet-based tool was created that can help the process of measuring the height and weight of toddlers in posyandu to be easier, faster, and more accurate. The data can also help posyandu officers, medical personnel, and parents in making decisions related to the health and nutrition of toddlers. Height and weight monitoring is done through a spreadsheet. The components used in this tool are ESP 8266 as a microcontroller, ultrasonic sensor as a height meter, load cell sensor as a weight meter, LCD to display measurement notifications, rfid-rc522 to communicate data from rfid tags so that when scanning/tagging to rfid, the data from height and weight measurements will be uploaded to the spreadsheet. From the tests carried out, it is obtained that the device functions properly and helps posyandu officers to monitor and measure the growth of height and weight in toddlers efficiently.